Hughes syndrome and epilepsy: when to test for antiphospholipid antibodies?. (November 2016) - Noureldine, M H A; Harifi, G; Berjawi, A; Haydar, A A; Nader, M; Elnawar, R; Sweid, A; Al Saleh, J; Khamashta, M A; Uthman, I
Epilepsy and seizures are reported among the neurological manifestations of antiphospholipid syndrome (APS) at a prevalence rate of approximately 8%, which is nearly 10 times the prevalence of epilepsy in the general population. The association of seizures with antiphospholipid antibodies (aPL) is even more significant in the presence of systemic lupus erythematosus (SLE). In this review, we discuss the epidemiological, pathophysiological, laboratory, clinical, and radiological aspects of this association, and derive suggestions on when to consider testing for aPL in epileptic patients and how to manage seizures secondary to APS based on literature data. Epilepsy due to APS should be considered in young patients presenting with seizures of unknown origin. Temporal lobe epilepsy seems to be particularly prevalent in APS patients. The pathogenesis is complex and may not only involve micro-thrombosis, but also a possible immune-mediated neuronal damage. Patients with seizures and positive aPL tend to develop thrombocytopenia and livedo racemosa more frequently compared with those without aPL. Magnetic resonance imaging (MRI) remains the imaging modality of choice in these patients. The presence of SLE and the presence of neurological symptoms significantly correlate with the presence of white matter changes on MRI. In contrast, the correlation between aPL positivity and the presence of white matter changes is very weak. Furthermore, MRI can be normal in more than 30–40% of neuropsychiatric lupus patients with or without aPL. aPL testing is recommended in young patients presenting with atypical seizures and multiple hyper-intensity lesions on brain MRI in the absence of other possible conditions. New MRI techniques can better understand the pathology of brain damage in neuro-APS. The therapeutic management of epileptic APS patients relies on anti-epileptic treatment and anticoagulant agents when there is evidence of a thrombotic event. In the absence of consensual recommendations, the decision of lifelong anticoagulation is discussed on a case-by-case basis. The anti-thrombotic benefit of hydroxychloroquine and statins is supported by several studies.